Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1080/13607863.2014.962009
|View full text |Cite
|
Sign up to set email alerts
|

Leisure, functional disability and depression among older Chinese living in residential care homes

Abstract: These results provide support for the mediating and moderating roles of leisure in the stress-health relationship among institutionalized elders. To enhance residents' psychological health, residential care homes are recommended to organize more leisure activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 41 publications
0
27
0
1
Order By: Relevance
“…This might be the reason that Chinese institutional elders’ physical health status tends to be poorer than that of community‐dwelling elders (Ouyang et al . ). Additionally, according to previous studies, physical health problems could reduce elders’ self‐esteem by impairing their self‐care ability and self‐independence (Chen ) and exposing more obstacles and limitations in their daily life (Franak et al .…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…This might be the reason that Chinese institutional elders’ physical health status tends to be poorer than that of community‐dwelling elders (Ouyang et al . ). Additionally, according to previous studies, physical health problems could reduce elders’ self‐esteem by impairing their self‐care ability and self‐independence (Chen ) and exposing more obstacles and limitations in their daily life (Franak et al .…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies showed that the main reasons for Chinese elderly entering nursing homes were decline in physical function, limited selfcare ability, and lack of family caregivers (Gu et al 2007). This might be the reason that Chinese institutional elders' physical health status tends to be poorer than that of community-dwelling elders (Ouyang et al 2015). Additionally, according to previous studies, physical health problems could reduce elders' self-esteem by impairing their self-care ability and self-independence (Chen 1996) and exposing more obstacles and limitations in their daily life (Franak et al 2015).…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations